Organizational Management Based on Persuasive Communication - Fazli Abdillah Abdillah; Nasrul Syakur Chaniago (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
This article aims to analyze how persuasive communication is applied in organizational management at MAS Al-Washliyah 22 Tembung and how it influences organizational effectiveness. This research uses a qualitative method with a case study approach. Data was obtained through in-depth interviews with administrators and members of MAS Al-Washliyah 22 Tembung, participant observation, and documentation. This research shows that persuasive communication is applied in various aspects of organizational management at MAS Al-Washliyah 22 Tembung, such as planning, organizing, mobilizing and supervising. Effective persuasive communication has been proven to increase member motivation and participation, as well as strengthen a sense of togetherness and commitment to the organization. The application of effective persuasive communication in organizational management at MAS Al-Washliyah 22 Tembung has been proven to increase the effectiveness of the organization in achieving its goals. These research findings hold significant implications for organizational management practices in Islamic schools, offering valuable insights into how persuasive communication can enhance management practices in such educational institutions. By implementing these research findings, Islamic schools can enhance educational quality and achieve their goals more effectively.